Impacts of In-Accessible and Poor Public Transportation System on Urban Enviroment: Evidence from Hyderabad, Pakistan - Jawed, A.; Talpur, M. A. H.; Chandio, I. A.; Mahesar, P. N. (Engineering, Technology & Applied Science Research, 2019)
City design plays a major role in the way of life of its inhabitants. The growth of urban centers requires careful schemes to ascertain that the quality of life is not adversely influenced. The rate of motorization is increasing in Hyderabad, Pakistan due to inaccessible public transportation. An efficient public transportation system performs a critical part in sustaining and improving urban welfare by providing access to daily necessities. The basic aim of this study is to discuss the impacts of inaccessible public transportation on urban population, the environmental effect of recent urban transport designs, and the expansion in traffic congestion. Landsat images were used to highlight the existing public transportation routes and dynamic and more realistic travel distances and times were measured. Data were collected from local households and further frequency analysis was done through SPSS. The outcome of this research may assist the evolution of a sustainable and accessible transportation system for the urban population.